HUBUNGAN MINAT BACA TERHADAP KEMAMPUAN MENULIS PUISI PADA PESERTA DIDIK DI SD GUNUNG SINDUR - Aulia Qathrun Nada (Universitas Muhammadiyah Purwokerto, 2023)
The relationship between reading interest and poetry writing ability at SD Gunung Sindur was motivated by a research hypothesis which suspected that there was a relationship between reading interest and poetry writing ability in fifth grade students. This research was conducted at SDN Cidokom 03 Gunung Sindur Bogor. This study uses a quantitative approach with correlational methods using questionnaires, tests and documentation as instruments. The research population used in this study were all fifth grade students, while the research sample used in this study were fifth grade students at SDN Cidokom 03, totaling 30 respondents. Sampling using saturated sampling technique. The instruments given were a questionnaire and a test using a questionnaire for reading interest and using a written test to write poetry. Data analysis using Pearson Correlation Test. This is proven by the results of calculations showing the results of the Pearson Correlation test showing that reading interest (X) with students' poetry writing ability (Y) is 0.007 smaller than the value of 0.05 (0.007 < 0.05). For the level of relationship, the Pearson correlation value is 0.486, this indicates that reading interest. has a fairly strong relationship with the ability to write poetry. Thus, it can be concluded that there is a relationship between students' reading interest and the ability to write poetry at SDN Cidokom 03.